Analisis Kemampuan Literasi Matematika Mahasiswa pada Mata Kuliah Statistika Inferensial Ditinjau dari Gaya Belajar - Aprilia Nurul Chasanah; Arief Budi Wicaksono; Sherlya Nurtsaniyah; Rivka Nur Utami (Edumatica : Jurnal Pendidikan Matematika, 2020)
The mathematics literacy abilities are strongly needed for the students to be able to face educational challenges from the cognitive aspects. The students' mathematics literacy abilities can be viewed from various dimensions, one of whixzch is the learning styles. The purpose of this research is to analyze the students' mathematics literacy abilities in inferential statistics subject based on the learning styles. This is a qualitative descriptive research. The subjects of this research are the fourth semester students at a higher education institution in Magelang, Central Java, Indonesia, who are currently taking inferential statistics course. The instruments used in this research are test and interview instruments. The data analysis is carried out through data reduction, data presentation, and drawing conclusions. The students’ mathematics literacy abilities with divergent learning styles are only able to arrive at the formulating step. The students’ mathematics literacy abilities with convergent learning styles are able to take the mathematical literacy processes. The students' mathematics literacy abilities in the assimilation learning style have come to the interpreting step, but they have not been able yet to solve the problems well. The students' mathematics literacy abilities in the accommodation learning style have been able to understand and check (formulating and interpreting) well but in preparing plans or arguing (employing stage) in solving the problems, it has not been achieved yet properly. Based on the research results, it is found that each different learning style has its own different mathematics literacy abilities